(untitled) (Research, Society and Development, 2022)
Species belonging to the genus Spirulina are among the most commercially important photosynthetic microorganisms. This work aimed to evaluate the cultivation of Spirulina platensis and Spirulina maxima with partial replacement of synthetic medium by RM (barley malt residue) as well as to extract bioactive compounds applicable to the food industry. Growth parameters, biomass composition, concentrations of proteins, carbohydrates, lipids, fatty acids, phycocyanin extraction, polysaccharides and monosaccharides were evaluated. The cultures using RM at a concentration of 50% obtained growth equivalent to the control. The chlorophyll content was higher for the two Spirulina species grown in the control medium. Phycocyanin levels were higher for Spirulina platensis. The highest protein contents were found for Spirulina platensis (55.9g 100g-1) followed by Spirulina maxima (53.3g 100g-1) cultivated in RM. The polyunsaturated linoleic and alpha-linolenic acids showed higher percentages in the strains cultivated in MR. The PUFA content was higher in cultures in RM medium, ranging from 57 to 59%. The extraction of polysaccharides with hot water/ultrasound showed higher values ​in the two species grown in RM medium, ranging from 8.3 to 11.2%. The content of exopolysaccharides was highlighted in the culture with RM medium (191 to 193mg·L-1) for both species. The results show that the use of malt residue as a partial substitute for the control medium is suitable as an alternative medium for the cultivation of Spirulinas platensis and maxima. In addition, the potential of its bioactive compounds for the food industry is highlighted.